Effect of Carbon Emission Disclosure on Company Value with Environmental Performance as Moderating Variable in Non–Financial Companies Listed on the Indonesian Stock Exchange - Andi Khaerun Nisa (JEKAMI Journal of Accounting, 2023)
This study aims to examine the effect of environmental performance in strengthening the relationship of carbon emissions' disclosures to firm value in non–financial companies listed on the Indonesia Stock Exchange. The research population used is non–financial companies listed on the Indonesia Stock Exchange for the period 2019 to 2021. The sampling technique in this study uses the purpose sampling method and obtained a number of 75 companies as research samples. The analytical method used is moderate regression analysis. The results of this study indicate that the variable carbon emission disclosure has a positive and significant partial effect on firm value. And the interaction variable of carbon emission disclosure with environmental performance weakens the effect of the variable carbon emission disclosure on company value.